1999
DOI: 10.1007/pl00012366
|View full text |Cite
|
Sign up to set email alerts
|

Primary Retroperitoneal Soft Tissue Sarcomas: Results of Aggressive Surgical Treatment

Abstract: A retrospective study was undertaken to evaluate the results of surgical treatment in a series of patients with primary retroperitoneal sarcomas consecutively treated by the same surgical team. The hospital records of 42 patients with primary retroperitoneal sarcomas who underwent surgical exploration at our unit from 1984 to 1995 were reviewed. A univariate analysis was used to identify the main clinical, pathologic, and treatment-related factors affecting long-term survival. Twenty-five patients (59.6%) unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 9 publications
0
21
1
5
Order By: Relevance
“…Thus, it is often difficult to obtain a margin of normal tissue around the tumor [13]. Complete resection varies from 38 to 74% in most reports [3,9,15]. The rate of complete resection in this study was 66.7%.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Thus, it is often difficult to obtain a margin of normal tissue around the tumor [13]. Complete resection varies from 38 to 74% in most reports [3,9,15]. The rate of complete resection in this study was 66.7%.…”
Section: Discussionmentioning
confidence: 53%
“…Patients with RSTS tend to have a poor prognosis with a high local recurrence rate and a low 5-year survival rate [1,2,5]. Surgery is the principal mode of therapy and offers the most favorable prognosis after complete resection [1][2][3]6]. In this study, we aimed to evaluate the morbidity, the mortality, and the prognostic factors that affect survival of the patients with RSTS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histological subtype appeared to influence the pattern of recurrence, which was mainly local for patients with liposarcoma. Several authors have noted that tumor negative surgical margins are associated with a reduced risk of local recurrence and improved disease specific survival, especially in patients with low-grade retroperitoneal LPS (1,3,4). In both our case only limited involvement of renal parenchyma was observed at the time of surgery, which made renal sparing surgery a feasible option without compromising the oncological principle of tumor free margins.…”
Section: Commentsmentioning
confidence: 51%
“…In general, the biological behavior and prognosis of liposarcomas (LPS) are more favorable compared to most soft tissue sarcomas (STS) but the prognosis can vary widely depending on tumor characteristics, especially histological subtype and tumor grade (3). Emphasizing the importance of radical resection and tumor negative surgical margins for disease specific survival, these tumors have traditionally been treated with radical surgery sacrificing adjacent organs (1,(3)(4)(5). Multiple trials of chemotherapy and radiation therapy have shown no survival benefit.…”
Section: Introductionmentioning
confidence: 99%